Análise e desenvolvimento de novas configurações de antenas, filtros e superfícies seletivas de frequência não-uniformes e reconfiguráveis pelo método WCIP generalizado - Silva Neto, Valdemir Praxedes da (2016)
The modern communications systems require devices with high operating performance. For the supply of this demand, it is essential to develop new devices that are lightweight, low cost, showing ease of construction and ability to integrate with other circuits that make up the system completely. Thus, new configurations of integrated microwave circuits increasingly attract the attention of researchers, the good performance in the integration and prototyping of transmitting and receiving wireless signals systems. This paper proposes and details the application of a numerical technique, consisting of a full-wave formulation, based on the concept of electromagnetic waves and the principle of reflection and wave transmission circuit in the interface: Wave Concept Iterative Procedure (WCIP). The method Wave Concept Iterative Procedure (WCIP) or waves iterative method is presented as a tool with high precision in planar circuits study microwave. New configurations are proposed antenna structures, filters, and frequency selective surfaces. For antennas, antennas are presented with random fractal patch in traditional settings and how monopole, response analysis are performed in frequency of such printed antennas in different dielectric substrate, including textiles. Results for resonance frequency, bandwidth, return loss and radiation pattern were obtained and discussed. Two planar filter settings were presented. Their synthesis and characterization of the frequency response were presented and carried out by applying the method WCIP. Results for its frequency response are shown. FSS different settings are presented in this thesis, such as: FSS with fractal elements, reconguráveis and FSS based on non-uniform arrangement of elements. Some prototypes of the devices proposed in this thesis were built and the experimental results showed the mathematical model presented. The results were also compared with the Ansoft HFSS simulation results, it was observed a good correlation between them.